Survey of European Nuclear Policy, 1985-87
XII, 158 p.
Keywords: An analysis of the extent to which European countries have progressed towards a nuclear non-proliferation policy. It reviews the policies of six specific countries and surveys present trends. The book suggests ways of improving policy in view of the increasingly unstable world outlook.